Impact of Distance to Treatment Center on Care Seeking for Pelvic Floor Disorders. Issue 6 (November 2017) - English, Emily; Rogo-Gupta, Lisa
Abstract : Objective: The aim of this study was to evaluate the impact of distance from residence to treatment center on access to care for female pelvic floor disorders at an academic institution. Methods: A retrospective cross-sectional study was conducted of women seen for pelvic floor disorders at an academic institution from 2008 to 2014. Patient characteristics were extracted from charts. Geographical and US census data was obtained from public records and used to calculate distance from patient residence to physician office. Statistical analysis was performed using R Software (Version 0.98.1102) and Microsoft Excel (Version 14.4.7). Statistical significance was defined as a 2-sided P value of less than 0.05, and the χ 2 test was used to determine associations of categorical variables. Results: A total of 3015 patients were included in the analysis. The mean distance traveled was 93 miles. Thirty percent of patients traveled more than 50 miles. Many patients (43%) reported having the symptoms for more than 2 years. Patients who traveled farther were significantly more likely to be white, English-speaking, and with pelvic organ prolapse as primary complaint. These patients were more likely to plan surgery at the first visit than patients who traveled less far (29% vs 14%). Patients who traveled farther were also more likely to live in counties with a low percentage of persons older than 65 years and low percentage of female inhabitants. Conclusions: Women who travel the farthest for treatment of pelvic floor disorders have experienced the symptoms for longer duration and are more willing to plan surgery at presentation. These women also come from counties with fewer elderly women, suggesting future outreach care should focus on similar geographic areas. Abstract : This is a retrospective study that demonstrates that women travel great distances for treatment of PFDs; those who travel the farthest tend to have a longer duration of symptoms and are more likely to plan surgery at the initial clinic visit.